Estimating the end-of-life of PEM fuel cells: Guidelines and metrics - Jouin, Marine; Bressel, Mathieu; Morando, Simon; Gouriveau, Rafael; Hissel, Daniel; Péra, Marie-Cécile; Zerhouni, Noureddine; Jemei, Samir; Hilairet, Mickael; Ould Bouamama, Belkacem (Applied energy, 2016)
•A methodology for prognostics of PEMFC is discussed.•Procedures for data selection and processing are proposed.•Health indicators and EoL thresholds are discussed.•Issues regarding the SoH definitions are highlighted.•New prognostics’ metrics dedicated to PEMFC are built. Prognostics applications on PEMFC are developing these last years. Indeed, taking decision to extend the lifetime of a PEMFC stack based on behavior and remaining useful life predictions is seen as a promising solution to tackle the too short life’s issue of PEMFCs. However, the development of prognostics shows some lacks in the literature. Indeed, performing prognostics requires health indicators that reflect the state of health of stack, while being able to interpret them in an industrial context. It is also important to propose criteria to set its end of life. Moreover, to trust any prognostics’ application, one should be able to evaluate the performance of its algorithms with respect to standards. To help launching a discussion on these subjects among scientific and industrial actors, this paper addresses some of the issues encountered when performing prognostics of a PEMFC stack. After showing the link between prognostics and decision, this paper proposes guidelines to set the limits of a prognostics approach. The definitions of healthy and degraded modes are discussed as well as how to choose the time instant to perform predictions. Then, three criteria based on the power produced by the stack are proposed as indicators of the state of health of the stack. The definition of the end of life of the stack is also discussed before proposing some criteria to assess the performance of any prognostics algorithm on a PEMFC. Some perspectives of works are also discussed before concluding.